Desulfurization gypsum carbonation for CO2 sequestration by using recyclable ammonium salt. (February 2023) - Ding, Wenjin; Qiao, Jingyi; Zeng, Li; Sun, Hongjuan; Peng, Tongjiang
Highlights: NH4 Cl is used to leach Ca 2+ from FGD gypsum and can be used for seven times. 1 ton of FGD gypsum absorbs 207 kg of CO2 while producing 470 kg of CaCO3 . High-purity CaCO3 with different grain size, structure and morphology is successfully produced. Carbonation parameters can affect the polymorphism of CaCO3 . Abstract: Based on salt effect and the solubility equilibrium theory of insoluble electrolyte, the technological process of ammonia-enhanced desulfurization gypsum carbonation for CO2 sequestration in NH4 Cl-H2 O system was studied, and calcium carbonate with different crystal phase and morphology was prepared in this paper. The results showed that the optimal conditions for the dissolution of Ca 2+ included NH4 Cl concentration of 4 mol/L, LS of 80:1 mL/g, leaching temperature and time of 50 °C and 60 min. The optimal leaching rate was 95.6%, and the leaching residue could be used for cement production. Regarding the optimum conditions of carbonation reaction, the addition amount of ammonia was 10 mL, CO2 flow rate was 80 mL/min, reaction temperature was 40 °C, reaction time was 60 min, and the carbonation conversion rate was 98.54%. The filtrate of carbonation reaction could be recycled for 7 times, and the reaction efficiency was 50.8%. The optimal carbonated product was rhombohedral calcite, and the performance of the product was beyond the requirements of HG/T 2226–2010. The reaction conditions had little influence on the phase and microscopic morphology of the carbonated products. The proposed research is expected to be applied to the CO2 sequestration and the utilization of desulfurization gypsum. Graphical abstract: Image, graphical abstract